1998
DOI: 10.1021/ac971184b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sampling Rate on Resolution in Comprehensive Two-Dimensional Liquid Chromatography

Abstract: In “comprehensive” two-dimensional liquid chromatography, the column effluent from the first separation system (the first dimension) is sequentially sampled by the second dimension separation system. The total analysis time is largely determined by the speed of the second dimension separation system; the most retained component must elute before the least retained component of the next second dimension separation. Optimization of multidimensional separation systems requires that one understand the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
321
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 434 publications
(331 citation statements)
references
References 21 publications
(16 reference statements)
9
321
1
Order By: Relevance
“…-all sample components are subjected to two separations in which their displacement depends on different factors; -any two compounds separated in the first dimension must remain separated in the second dimension (this objective is achieved with at least three or four modulations per peak); -the elution profiles from both dimensions are maintained (Giddings, 1987;Murphy, Schure, & Foley, 1998;Schoenmakers, Marriott, & Beens, 2003).…”
Section: A Modulation Processmentioning
confidence: 99%
“…-all sample components are subjected to two separations in which their displacement depends on different factors; -any two compounds separated in the first dimension must remain separated in the second dimension (this objective is achieved with at least three or four modulations per peak); -the elution profiles from both dimensions are maintained (Giddings, 1987;Murphy, Schure, & Foley, 1998;Schoenmakers, Marriott, & Beens, 2003).…”
Section: A Modulation Processmentioning
confidence: 99%
“…In comprehensive two-dimensional chromatography, a short sampling time in the second dimension is prerequisite to obtain high two-dimensional resolution. This means that each separated peak in the first dimension should be split into at least three or four fractions in the second dimension [18][19]. In our experiments, the short modulation time, e.g., 4 s, for the first dimension retention time causes multiple peak entries for one chromatographic peak generated by one metabolite.…”
Section: Algorithmmentioning
confidence: 99%
“…Murphy and co-workers [111] and Seeley [112] studied the effect of sampling rate on resolution in LC×LC, with both groups coming to the same conclusion that when the first dimension peak is sampled a minimum of three times, the loss in resolution is minimal. In a later study by Horie and co-workers [113], it was shown that the best compromise between sampling rate and second dimension analysis time in on-line LC×LC can be achieved when each first dimension peak is sampled a minimum of two times.…”
Section: Peak Capacity Sampling Frequency and Orthogonalitymentioning
confidence: 99%